Study protocol of REpeat versus SIngle ShoT Antibiotic prophylaxis in major Abdominal Surgery (RESISTAAS I): a prospective observational study of antibiotic prophylaxis practice for patients undergoing major abdominal surgery - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Teroerde, Miriam; Rau, Heike; Frey, Otto Roman; Hornuß, Daniel; Billeter, Adrian; Klotz, Rosa; Chiriac, Ute; Larmann, Jan; Weigand, Markus A.; Probst, Pascal; et al. (BMJ open, 2022)
Introduction Surgical site infections (SSIs) are among the most common complications after abdominal surgery and develop in approximately 20% of patients. These patients suffer a 12% increase in mortality, underlying the need for strategies reducing SSI. Perioperative antibiotic prophylaxis is paramount for SSI prevention in major abdominal surgery. Yet, intraoperative redosing criteria are subjective and whether patients benefit from it remains unclear. - Methods and analysis The REpeat versus SIngle ShoT Antibiotic prophylaxis in major Abdominal Surgery (RESISTAAS I) study is a single-centre, prospective, observational study investigating redosing of antibiotic prophylaxis in 300 patients undergoing major abdominal surgery. Adult patients scheduled for major abdominal surgery will be included. Current practice of redosing regarding number and time period will be recorded. Postoperative SSIs, nosocomial infections, clinically relevant infection-associated bacteria, postoperative antibiotic treatment, in addition to other clinical, pharmacological and economical outcomes will be evaluated. Differences between groups will be analysed with analysis of covariance. - Ethics and dissemination RESISTAAS I will be conducted in accordance with the Declaration of Helsinki and internal, national and international standards of GCP. The Medical Ethics Review Board of Heidelberg University has approved the study prior to initiation (S-404/2021). The study has been registered on 7 February 2022 at German Clinical Trials Register, with identifier DRKS00027892. We plan to disseminate the results of the study in a peer-reviewed journal. - Trial registration German Clinical Trials Register (DRKS): DRKS00027892.
Gesehen am 13.12.2022